Effects of Pilates Training on Physiological and Psychological Health Parameters in Healthy Older Adults and in Older Adults With Clinical Conditions Over 55 Years: A Meta-Analytical Review - Meikis, Lilly; Wicker, Pamela; Donath, Lars (Frontiers in Neurology, 2021)
This meta-analytical review aimed at comparing the impact of Pilates interventions (PIs) on physiological and psychological health parameters in healthy older adults and older adults with a clinical condition aged 55 years and older. The literature search was conducted in three databases (PubMed, Web of Science, SPORTDiscus). Randomized controlled trials that aimed at improving physiological and psychological health parameters in adults aged 55 years and older using Pilates as an intervention were screened for eligibility. The included data was extracted and assigned based on participants' health condition (clinical vs. non-clinical), as well as the respective control condition used in the study [inactive (IC) vs. active control group (AC)]. Statistical analyses were computed using a random-effects inverse-variance model. Fifty-one studies with a total of 2,485 participants (mean age: 66.5 ± 4.9 years) were included. Moderate effects (SMD: 0.55; 0.68) were found for physiological health parameters (muscle strength, balance, endurance, flexibility, gait, and physical functioning) in both experimental (clinical and non-clinical) conditions when compared to ICs (p < 0.003; p = 0.0001), and small to moderate effects (SMD: 0.27; 0.50) when compared to ACs (p = 0.04; p = 0.01). Moderate to large effects (SMD: 0.62; 0.83) were documented for psychological health parameters (quality of life, depression, sleep quality, fear of falling, pain, and health perception) in both conditions when compared to ICs (p < 0.001, p < 0.001). PIs induce small to large effects in physiological and psychological health parameters in older adults, regardless of their health condition. The substantial heterogeneity within the included studies complicated standardized comparison of the training modalities between the two target groups. Nonetheless, Pilates seems to be a safe, adaptable, and promising exercise approach for a heterogenous population of older adults.